The Stationary Banding Complex and Secondary Eyewall Formation in Tropical Cyclones. Issue 6 (12th March 2020) - Vaughan, Anna; Walsh, Kevin J. E.; Kepert, Jeffrey D.
Abstract: 89 GHz passive microwave satellite data are used to develop a five year climatology of the incidence and morphology of the stationary banding complex in tropical cyclones and quantify changes in convective morphology prior to secondary eyewall formation. The stationary banding complex is shown to be present in 39% of passive microwave overpasses. Morphology varies substantially between tropical cyclones, with crossing angles ranging from 0.19° to 61.78° and azimuthal extents from 0.29 π to 4.02 π radians. Variations in the incidence and geometry of the stationary banding complex are observed in different environmental conditions and geographic locations. For 84 secondary eyewall formation events included in the sample, a stationary banding complex is observed within 6 hr of the secondary eyewall developing in 79% of cases. Within 12 hr prior to secondary eyewall formation, the crossing angle is significantly lower than its sample median, while the azimuthal extent is higher than its sample median. These results demonstrate that secondary eyewall formation is (most) often preceded by the formation and axisymmetrization of a stationary banding complex. Key Points: A stationary banding complex is observed in 39% of passive microwave images of tropical cyclones A stationary banding complex is observed within 6 hr of secondary eyewall formation in 79% of events Stationary banding complex crossing angle (azimuthal extent) is significantly lower (higher) within 12 hr of secondary eyewall formation